Accounting for the "transcendent self": spirituality, narcissism, testimony and gift. Issue 2 (24th August 2021) - Achilli, Giulia; Busco, Cristiano; Giovannoni, Elena
Abstract : Purpose: The paper explores the process of construction of the "accountable self", particularly as this process engages with the spirituality of the self. This study examines the "space of accountability" within which the accountable self constructs itself as such and investigates how different accounts of the self are drawn upon in the making of this space, both defining and transcending it. Design/methodology/approach: The paper relies upon archival material concerning accounting and accountability practices about the project for building the altar of St. Ignatius in the Church of Gesù, Rome, Italy (1691–1706). This study examines calculative and narrative accounts about the project from the perspective of the superintendent, who was the sole person accountable for the building works. Findings: Whereas calculative accounts enabled the self to account for actions within the specific space of accountability of the project, narrative accounts opened up this space, providing for a testimony of actions and a gift of accountability towards future indefinite others. This process was prompted by the spirituality of the self and the narcissistic gratification of fulfilling this spirituality. Originality/value: The paper adds to the literature on the accountable self and to theological perspectives into accountability. This study suggests exploring how different accounts of the self engage with each other through testimony, gift, narcissism and spirituality in the construction of the accountable self, providing for a "transcendent" space of accountability. This research also adds to studies on narrative accounts by showing that they are drawn upon alongside calculative accounts in the construction of the transcendent, accountable self.